Effect of social media use on food safety risk perception through risk characteristics: Exploring a moderated mediation model among people with different levels of science literacy - Zhang, Jie; Wu, Hsi-Chen; Chen, Liang; Su, Youzhen (Frontiers in Psychology, 2022)
Food safety risk (FSR) is becoming a vital issue for public health and it is necessary to improve the public awareness of FSR though social media. Aims at exploring specific mechanisms of FSR perception, this study first categorizes 19 risk characteristics into two variables—dread/efficacy; and then examines how social media use affect perceived FSR through the two risk variables. Additionally, this study explores the moderating effects of source credibility and science literacy on the mechanisms of FSR perception. Based on a nationwide online survey (N = 2015) over six salient food safety issues in China, the current study found that exposure to food safety risk information on social media can help to improve perceived FSR based on the proposal “dread-efficacy processing model” (DEPM) where dread stimulates perceived risk while efficacy suppresses risk perception. Moreover, source credibility intensifies the effect of social media use on efficacy appraisal whereas science literacy exerts a “double-weakening” influence on dread appraisal. Theoretical and practical implications of findings are discussed.